Synthesis and characterization of polyesters from 2,3-bis (4 `-hydroxy phenyl) quinoxaline and 2,3-bis (2 `-hydroxynaphthalene-6 `-yl) quinoxaline - Patil, V. B.; Medhi, M.; Bhairamadgi, Nagendra S.; Wadgaonkar, P. P.; Maldar, Noormahamad N. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
Two bisphenols containing pendant, quinoxaline moiety; 2,3-bis (4'-hydroxy phenyl) quinoxaline (BHPQ) and 2,3-bis (2'-hydroxynaphthalene-6-yl) quinoxaline (BHNQ) were synthesized and characterized by FT-IR, (1)H, (13)C NMR and mass spectrometry. Aromatic polyesters and copolyesters were prepared by interfacial polymerization from BHPQ or BHNQ and isophthaloyl chloride or terephthaloyl chloride or a mixture of different mole proportions of (IPC + TPC). These polyesters and copolyesters were characterized by spectroscopic technique, viscosity measurement, solubility, thermal stability. DSC and XRD. Polymers had moderate to high molecular weights as evidenced by the inherent viscosities in the range 0.35-0.78 dL/g for BHPQ series and 0.27-0.52 dL/g for BHNQ series. BHPQ polyesters and copolyesters dissolved in m-cresol, NMP and conc. H(2)SO(4) whereas, BHNQ polyesters and copolyesters were readily soluble in NMP, DMAc, (TCE + phenol) and partly soluble in solvent like CHCl(3), pyridine, etc. Wide angle X-ray diffraction (WAXD) results showed that introduction of quinoxaline moiety into polymer chain and aromatic phenyl/rigid naphthyl structures lead to crystalinity. Differentional scanning calorimetry of BHNQ polyesters showed the glass transition temperatures in the range of 131-151 degrees C. BHPQ polyesters did not show any weight loss below 330 degrees C and retained 27-55% weight at 900 degrees C when investigated by TGA under nitrogen atmosphere demonstrating good thermal stability BHNQderived polyesters showed initial decomposition temperatures in range 211-234 degrees C. The structure-property relationships for the mentioned polyesters are analyzed, as these polyesters are of interest as materials for electronics, microelectronics and membrane separation. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: 2; 3-Bis (2 `-hydroxynaphthalene-6 `-yl) quinoxaline; 3-Bis (4 `-hydroxy phenyl) quinoxaline; Aromatic polyesters; Glass transition temperature; solubility; Thermal properties

Enhanced energy density and stability of self-assembled cauliflower of Pd doped monoclinic WO3 nanostructure supercapacitor - Gupta, S. P.; Patil, V. B.; Tarwal, N. L.; Bhame, S. D.; Gosavi, S. W.; Mulla, I. S.; Late, D. J.; Suryavanshi, S. S.; Walke, P. S. (Materials Chemistry and Physics, 2019)
Enhanced electrochemical performance of WO3 nanostructures by engineering their morphology, structural and surface defect at nanoscale is feasible. Herein we report the effect of Pd doping on the morphological and electrochemical properties of WO3 at nanoscale prepared by a simple hydrothermal method. The synthesized pristine WO3 (cabbage like morphology) and Pd doped WO3 (cauliflower like morphology) are examined by using XRD, XPS, Raman spectra, BET, FE-SEM, TEM. The morphological investigation shows the effective rebuilding of nanosheets assembled cabbage shaped pristine WO3 into nanobricks assembled cauliflower shaped Pd doped WO3 with improvement in crystallinity, surface area and conductivity. As a result, the enhancement in the electrochemical performance of cauliflower shaped Pd-WO3 is recorded four times higher specific capacitance than pristine WO3. Additionally, the excellent cyclic stability (almost ten times higher than pristine WO3) up to 1100 cycles with nearly 86.95% capacity retention is observed in Pd-WO3 attributed to Pd content and highly modified structural arrangement.

2-D to 3-D conversion of WO3 nanostructures using structure directing agent for enhanced NO2 gas sensing performance - Beknalkar, S. A.; Patil, V. L.; Harale, N. S.; Suryawanshi, M. P.; Patil, A. P.; Patil, V. B.; Kim, J. H.; Patil, P. S. (Sensors and Actuators A-Physical, 2020)
An exotic 3-D tungsten oxide (WO3) microflower was synthesized via low-cost and environmental-friendly hydrothermal strategy. The effect of structure-directing agent on the formation of 3-D microflowers from a 2-D nanosheets of WO3 and its gas sensing behavior are investigated. The assynthesized WO3 powder was used in morphological, structural and phase studies by X-ray diffraction (XRD), scanning electron microscopy (SEM), FT-Raman spectroscopy and X-ray photoelectron spectroscopy (XPS). The WO3 samples were found to be polycrystalline with monoclinic crystal structure. The SEM micrographs revealed the formation of 3-D microflowers made up of two-dimensional (2-D) multi-directional dendritic nanoplates. The potassium hydroxide (KOH) acts as a structure-directing agent in the formation of 3-D microflowers of WO3 sample. To further understand the formation of 3-D microflowers of WO3 sample, concentration-dependent experiments were carried out by varying KOH concentration and the formation mechanism was investigated. The synthesized WO3 microstructures were subjected to detailed gas sensing tests for different gases at an optimized temperature. A selective, sensitive gas response was obtained for WO3 gas sensor. The lower detection limit is about 1 ppm at 150 degrees C working temperature for an optimized WO3 gas sensor. The gas sensing results indicate that the 3-D microflower-like WO3 nanostructures are highly promising for applications as gas sensors. (C) 2020 Published by Elsevier B.V.
Keywords: Microflowers; NO2 detection; WO3